Uterine arteriovenous malformation with repeated vaginal bleeding after dilatation and curettage - Da Joung Shim; Sang Joon Choi; Ji Min Jung; Ji Hyun Choi (Korean Society of Obstetrics and Gynecology, 2019)
Uterine arteriovenous vascular malformation (UAVM) is a disease that causes excessive bleeding. The symptoms do not subside without proper treatment and this can lead to life-threatening situations. The correct diagnosis of UAVM can be complicated if the patient's uterus did not completely discharge everything during abortion (in broader terms, retaining remnants of the products of conception). In this case, Doppler ultrasonography and computed tomography angiography with 3-dimensional rendering were used to analyze the cause of bleeding and provide proper treatment of this patient. Then, uterine artery embolization, dilatation, and curettage were performed safely and successfully. The patient no longer had symptoms of vaginal spotting during the planned follow up care. UAVM is uncommon; however, if reproductive-age women show repeated abnormal vaginal bleeding after dilatation and curettage, a diagnosis of UAVM must be considered based on the medical history and examination.